Avian Bornaviruses in Psittacine Birds from Europe and Australia with Proventricular Dilatation Disease - Weissenböck, Herbert; Bakonyi, Tamás; Sekulin, Karin; Ehrensperger, Felix; Doneley, Robert J.T.; Dürrwald, Ralf; Hoop, Richard; Erdélyi, Károly; Gál, János; Kolodziejek, Jolanta; Nowotny, Norbert (Emerging infectious diseases, 2009)
To determine whether avian bornaviruses (ABVs) were a factor in proventricular dilatation disease (PDD), we used immunohistochemistry, reverse transcription-PCR, and nucleotide sequence analysis to examine paraffin wax-embedded or frozen tissue samples of 31 psittacine birds with this disease. PDD is a fatal disease of psittacine birds associated with nonsuppurative encephalitis and ganglioneuritis of the upper intestinal tract. Tissue samples had been collected from 1999 through 2008 in Austria, Switzerland, Hungary, and Australia. Immunohistochemical demonstration of viral antigen within the brain and vegetative nerve system of the gastrointestinal tract provides strong evidence for a causative role of ABVs in this condition. Partial sequences of nucleoprotein (p40) and matrix protein (gp18) genes showed that virus in most of our cases belonged to the ABV-2 and ABV-4 groups among the 5 genogroups described so far. Viral sequences of 2 birds did not match any of the described sequences and clustered together in a new branch termed ABV-6.